A transcriptomic view of the ability of nascent hexaploid wheat to tolerate aneuploidy - Deying Zeng; Jiantao Guan; Jiangtao Luo; Laibin Zhao; Yazhou Li; Wenshuai Chen; Lianquan Zhang; Shunzong Ning; Zhongwei Yuan; Aili Li; Youliang Zheng; Long Mao; et al. (BMC Plant Biology, 2020)
Abstract Background In contrast to most animal species, polyploid plant species are quite tolerant of aneuploidy. Here, the global transcriptome of four aneuploid derivatives of a synthetic hexaploid wheat line was acquired, with the goal of characterizing the relationship between gene copy number and transcript abundance. Results For most of the genes mapped to the chromosome involved in aneuploidy, the abundance of transcripts reflected the gene copy number. Aneuploidy had a greater effect on the strength of transcription of genes mapped to the chromosome present in a noneuploid dose than on that of genes mapped elsewhere in the genome. Overall, changing the copy number of one member of a homeologous set had little effect on the abundance of transcripts generated from the set of homeologs as a whole, consistent with the tolerance of aneuploidy exhibited by allopolyploids, whether in the form of a chromosomal deficit (monosomy) or chromosomal excess (trisomy). Conclusions Our findings shed new light on the genetic regulation of homeoallele transcription and contribute to a deeper understanding of allopolyploid genome evolution, with implications for the breeding of polyploid crops.